PD-L1 targeted peptide demonstrates potent antitumor and immunomodulatory activity in cancer immunotherapy - Liang, Yulai; Luo, Huazao; Li, Xue; Liu, Shuang; Habib, Arslan; Liu, Baoxiu; Huang, Jiansheng; Wang, Jingbo; Yi, Han; Hu, Bo; Zheng, Liuhai; Xie, Jun; et al. (Frontiers in Immunology, 2024)
In recent years, immunotherapy has been emerging as a promising alternative therapeutic method for cancer patients, offering potential benefits. The expression of PD-L1 by tumors can inhibit the T-cell response to the tumor and allow the tumor to evade immune surveillance. To address this issue, cancer immunotherapy has shown promise in disrupting the interaction between PD-L1 and its ligand PD-1. We used mirror-image phage display technology in our experiment to screen and determine PD-L1 specific affinity peptides (PPL-C). In vitro, PPL-C has a strong affinity for PD-L1, with a binding rate of 0.75 M. T. An activation assay using T cells and mixed lymphocytes demonstrated that PPL-C inhibits the interaction between PD-1 and PD-L1. Using CT26 cells, we established a transplanted mouse tumor model to evaluate the inhibitory effects of PPL-C on tumor growth in vivo. PPL-C or an anti-PD-L1 antibody significantly reduced the rate of tumor mass development in mice compared to those given a control peptide (78% versus 77%, respectively). The results of this study demonstrate that PPL-C prevents or retards tumor growth. Further, immunotherapy with PPL-C enhances lymphocyte cytotoxicity and promotes proliferation in CT26-bearing mice. We also demonstrated that PPL-C inhibited the differentiation of T regulatory cells (Tregs) and regulated the production of cytokines. Based on the results of our experiment, PPL-C exhibited antitumor and immunoregulatory properties in the colon cancer. However, PPL-C peptides of low molecular weight could serve as effective cancer immunotherapy.